A Framework to Deal with Violence in South African Public Schools. (1st February 2016) - Baruth, Gayatri Devi; Mokoena, Sello
Abstract: Violence continues to be a major challenge in South African schools. The carrying of knives, guns and other weapons to school has become part of the daily life for many learners. These incidents highlight the extent of violence and crime experienced in South African communities, a factor which negatively impacts education and the maintenance of discipline in schools across the country. Despite the existence of official policies and protocols, violence, physical and sexual abuse, and gang activities are still the order of the day in many South African schools. Through an integrative literature review, this study proposes a model that can influence a review of the current policies with a view to overcoming the ongoing challenges and problems faced by many South African schools in dealing with violence. However, if nothing is done, violence at schools will continue to have a debilitating effect on effective teaching and learning.